Determinants of value added tax compliance in Thailand - Sangduang, Ranchida (2013)
The efficiency of Value Added Tax (VAT) procedure and system is important for levy on tax; the willing compliance in paying tax is main issue to improve tax collection. Understanding the factors that involve in VAT compliance. the Revenue Department will increase the proficiency in VAT registrants and collection process.This paper attempts to examine the factors that associated with VAT Compliance attitude.Data were collected through a survey of the result of entrepreneurs who are VAT registrant in Thailand.The multiple regression analysis was used to analyze the factors that determine VAT compliance attitude.The finding shows that there are a number of similarities with income tax compliance, with factors such as complexity and probability of detection appearing.The factors such a tax rate, record keeping, understanding and complexity are significant to determine VAT compliance whereas age of firm, nature of firm, size of firm, etc. are not significant.Furthermore, this research describes some problems of VAT comply that should be considered for improve VAT compliance. The results of this study are useful for policy makers to the extent each factor further which involves in VAT compliance and some problem of VAT comply. Not only VAT registrant more complies to pay tax but also non-registrant to become VAT registrant.